The Use of Augmented Reality Blended Learning for Improving Understanding of Food Security - Pujiastuti, H.; Haryadi, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The purpose of this study was to increase students’ understanding of the food security concept. The experimental method was being applied in this research. Moreover, research subjects were divided into two groups, one as an experimental group and another as a control group. The subjects of this study were 100 students at the Universitas Sultan Ageng Tirtayasa. Fifty students are guided under Augmented Reality based blended learning system as the experimental group. Another class of 50 students is on the control group, which studies with the conventional blended learning approach. The experimental class obtained 73% of the N-gain result, while control class obtained 50%. Therefore, it can be concluded that using augmented reality can improve the students’ understanding of the food security concept.